Risk factors of postoperative hypoparathyroidism after total thyroidectomy in pediatric patients with thyroid cancer - Yunsoo Choe; Yun Jeong Lee; Choong Ho Shin; Eun-Jae Chung; Young Ah Lee (Korean Society of Pediatric Endocrinology, 2022)
Purpose Hypoparathyroidism (hypoPTH) is the most common complication following thyroidectomy. We investigated the frequency and risk factors of hypoPTH after total thyroidectomy (TT) in pediatric patients with thyroid cancer. Methods This retrospective study included 98 patients younger than 20 years who were diagnosed with thyroid cancer after T T during 1990-2018 and followed for more than 2 years at Seoul National University Hospital. HypoPTH was defined as receiving active vitamin D (1-hydroxycholecalciferol or 1,25-dihydroxycholecalciferol) after surgery. Results The study included 27 boys (27.6%) and 71 girls (72.4%). The mean age at diagnosis was 14.9±3.7 years. HypoPTH occurred in 43 patients (43.9%). Twenty-one patients (21.4%) discontinued active vitamin D less than 6 months after surgery, while 14 (14.3%) continued active vitamin D for more than 2 years. Tumor multifocality (odds ratio [OR], 3.7 vs. single tumor; P=0.013) and preoperative calcium level (OR, 0.2; P=0.028) were independent predictors of hypoPTH immediately after TT. In addition, age (OR, 0.8; P=0.011) and preoperative calcium level (OR, 0.04; P=0.014) significantly decreased the risk for persistent hypoPTH requiring active vitamin D for more than 2 years. Conclusions HypoPTH occurred in 43.9% of pediatric thyroid cancer patients after TT in this study. Among them, one-third of patients continued active vitamin D medication for more than 2 years, which was predicted by young age and low preoperative calcium level.